Motivated beliefs in auctions - Tobias Riehm (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
In auctions bidders are usually assumed to have rational expectations with regards to their winning probability. However, experimental and empirical evidence suggests that agent's expectations depend on direct utility stemming from expectations, resulting in optimism or pessimism. Optimism increases ex ante savoring, while pessimism leads to less disappointment ex post. Hence, optimal expectations depend on the time left until the uncertainty is resolved, i.e. the time one can savor ex ante by being (too) optimistic. Applying the decision theory model of Gollier and Muermann (2010) to first price auctions, I show that by decreasing the time between bids and revelation of results, the auctioneer can induce bidders to forego optimism, leading to more aggressive bids and thereby higher revenues for the auctioneer. Finally I test these predictions experimentally, finding no evidence for my theoretical predictions.
Keywords: D44; C91; 330; Auctions; Experiment; Motivated Beliefs